(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
The objective of this research is to analyze the final sentences passed in an abbreviated procedure in terms of the requirement of motivation established by the Paraguayan Code of Criminal Procedure. For this purpose, firstly, it was developed from the background, the formalities and requirements that the parties must comply with, so that the jurisdictional organ prints the formalities for the application of the mentioned special procedure, which allows accelerating the conclusion of a trial before the same instance. Therefore, in order to achieve this objective, a qualitative approach was chosen, with a non-experimental documentary design. As for the data collection technique was the documentary analysis, consequently, a search and reading of the literature on the subject and final judgments of the virtual portal of the Supreme Court of Justice, during the month of December 2022 of the courts of the Central Department, for which sentences are imposed in this context, was carried out. In terms of scope, it was exploratory-descriptive. Among the main findings we have the analysis of five sentences passed in the framework of the mentioned procedure, of which three of them lacked sufficient motivation on the basis of the measurement of the penalty established in Art. 65 of the Penal Code. Finally, it is highlighted that two of them were dictated in punishable acts qualified as family violence as a reference to a judicial criminal policy, despite being considered a crime according to the classification established in art. 13 of the Penal Code.